Stereotactic Laser Ablation for Medically Intractable Epilepsy: The Next Generation of Minimally Invasive Epilepsy Surgery - LaRiviere, Michael J.; Gross, Robert E. (Frontiers in Surgery, 2016)
Epilepsy is a common, disabling illness that is refractory to medical treatment in approximately one third of patients, particularly among those with mesial temporal lobe epilepsy. While standard open mesial temporal resection is effective, achieving seizure freedom in most patients, efforts to develop safer, minimally invasive techniques have been underway for over half a century. Stereotactic ablative techniques, in particular radiofrequency ablation, were first developed in the 1960s, with refinements in the 1990s with the advent of modern computed tomography and magnetic resonance-based imaging. In the past 5 years, the most recent techniques have used MRI-guided laser interstitial thermotherapy (LITT), whose development began in the 1980s, saw refinements in MRI thermal imaging through the 1990s, and was initially used primarily for the treatment of intracranial and extracranial tumors. The present review describes the original stereotactic ablation trials, followed by modern imaging-guided radiofrequency ablation series for mesial temporal lobe epilepsy. The development of LITT and MRI thermometry are then discussed. Finally, the two currently available MRI-guided laser interstitial thermotherapy systems are reviewed for their role in the treatment of mesial temporal lobe and other medically refractory epilepsies.